2003
DOI: 10.1002/asmb.495
|View full text |Cite
|
Sign up to set email alerts
|

Thresholded scalogram and its applications in process fault detection

Abstract: SUMMARYScalograms provide measures of signal energy at various frequency bands and are commonly used in decision making in many fields including signal and image processing, astronomy and metrology. This article extends the scalogram's ability for handling noisy and possibly massive data. The proposed thresholded scalogram is built on the fast wavelet transform, which can capture non-stationary changes in data patterns effectively and efficiently. The asymptotic distribution of the thresholded scalogram is der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…To solve the eigen-value problem given in (10), as well as projecting the input space towards the kernel PCA space by employing (13), performing the nonlinear mappings can be evaded. In addition, both dot products can be computed in the feature space by bringing a kernel function as k(x, y) = ∅(x i ), ∅ x j [31,32].…”
Section: Principlementioning
confidence: 99%
See 1 more Smart Citation
“…To solve the eigen-value problem given in (10), as well as projecting the input space towards the kernel PCA space by employing (13), performing the nonlinear mappings can be evaded. In addition, both dot products can be computed in the feature space by bringing a kernel function as k(x, y) = ∅(x i ), ∅ x j [31,32].…”
Section: Principlementioning
confidence: 99%
“…This method allows us to detect errors in each of the scales and then to reconstruct the signals by keeping the significant scales (where the detection took place). A comparative analysis was performed between different approaches [30], which are: dissimilarity measure [31], multi-scale PCA [32], and moving PCA [33]. Implemented on the Tennessee Eastman process, the work showed that the multiscale PCA is superior to conventional methods in some cases and equivalent to them in others.…”
Section: Introduction and Bibliographical Reviewmentioning
confidence: 99%
“…The automated extraction of features from time-dependent complex QMS waveforms will ultimately lead to better process characterization and reduction of run-to-run process variability (Jeong et al 2003). By incorporating wavelets for process control, we obtain the following benefits: (1) dimensionality reduction through feature extraction of real-time QMS data, (2) automated detection of run-to-run incipient equipment faults to minimize variability, and (3) utilization of the wavelet transform's inherent time-localization properties for improved modeling of complex time-varying QMS waveforms.…”
Section: Illustrative Case Studymentioning
confidence: 99%
“…For example, functional data such as the rapid thermal chemical vapor deposition (RTCVD) signal, as presented in figure 2, are useful in process monitoring and improvement. Various other studies of functional data in fields such as semiconductor fabrication (Gardner et al 1997, Ganesan et al 2003, Jeong et al 2003, chemical manufacturing (Bakshi 1999), sheet-metal stamping (Jin and Shi 1999), and rotating machinery applications (Mori et al 1996, Urmanov et al 2002 demonstrate the utility of functional data.…”
Section: Introductionmentioning
confidence: 97%